Case report: POEMS syndrome with portal hypertension - Xu, Xiaotong; Jing, Changyou; Zhu, Tong; Jiang, Minjie; Fu, Yunlai; Xie, Fang; Li, Jianjun; Meng, Qinghua (Frontiers in Medicine, 2024)
This patient was an elderly patient with abdominal distension and shortness of breath. According to relevant examinations, his condition was initially considered to be related to cirrhosis, but pathological biopsy confirmed the diagnosis of noncirrhotic portal hypertension of unknown etiology. The portal vein pressure was significantly reduced after transjugular intrahepatic portosystemic shunt (TIPS). Nevertheless, the relief of the hydrothorax and ascites was not significant, and the numbness in both lower limbs gradually worsened. POEMS syndrome was ultimately diagnosed following a comprehensive examination. After two courses of bortezomib combined with dexamethasone, the patient died due to a systemic infection. The clinical symptoms of the patient were atypical, as was the presence of portal hypertension, which hindered the diagnosis of POEMS. Due to the patient’s advanced age, the diagnosis was delayed, and the prognosis was poor. This case reminds clinicians that POEMS patients can also have portal hypertension as the main manifestation.